Placental Epigenetics in Children’s Environmental Health - Marsit, Carmen J. (Semin Reprod Med, 2015)
There is a growing interest in understanding the mechanisms that drive the developmental origins of health and disease, and the role of epigenetic regulation has risen to the forefront of these studies. In particular, the placenta may be a model organ to consider as a mediator of the impact of the environment on developmental programming of children’s health, as this organ plays a critical role in directing development and regulating the fetal environment. Several recent studies have begun to examine how environmental toxicant exposures can impact the placental epigenome, focusing on studies of DNA methylation and microRNA expression. This review highlights several of these studies and emphasizes the potential the placenta may hold on the broader understanding of the impact of the intrauterine environment on long-term health.